Smart Tourism Entrepreneurship: The Role of Information Technology Infrastructure and the Digital Economic Ecosystem in Accelerating Local Entrepreneurship Development in Tourism Destinations - Nisa, Khairun; Astutiningsih, Sri Eka; Far Far, Risyart Alberth (Smart International Management Journal, 2026)
This research investigates the vital function of information technology (IT) infrastructure and digital economic ecosystems in driving the growth of local entrepreneurship across Indonesia's five Super Priority Tourism Destinations (DPSP). Employing a quantitative explanatory framework, the study analyzes secondary data from Statistics Indonesia (BPS), the Ministry of Tourism and Creative Economy, and Bank Indonesia spanning the 2022–2024 period to evaluate how connectivity influences the development of micro, small, and medium enterprises (MSMEs). The findings demonstrate a robust correlation (r = 0.782, p < 0.05) between IT infrastructure stability and the operational longevity of local firms, while the integration of digital payment ecosystems, notably QRIS, successfully mitigated entry barriers for 70,700 new merchants. However, the study identifies a persistent "Infrastructure-Human Gap," where technological readiness exceeds the digital literacy of local communities. The study concludes that fostering local entrepreneurial acceleration necessitates a strategic convergence of physical network expansion and human capital empowerment. Policy interventions should prioritize grassroots digital business incubation centers to guarantee inclusive and equitable tourism growth.